Stagnasi Ekonomi Dan Resistensi Masyarakat Jerman Terhadap Reformasi Negara Kesejahteraan - Krisantus Tobias Ghena Ona (Jurusan Ilmu Hubungan Internasional, 2016)
This paper aims at understanding why third way policy under Gerhard Schröder in Germany was failed. Since 2005, Germany was undergoing economic recession, marked by account deficit and slowing economic growth. At the same time the state had to face structural problems of welfare state such as unemployment. Why the third way proposal, failed to transformed welfare state system? This article pays attention on two structural problems; the moral hazard and non-wage labour cost. This article also shed a light on the resistance of the people towards welfare state transformation.